Zakat Dan Pajak Sebagai Instrumen Ekonomi Dalam Perspektif Moderasi Islam - Kuliman Kuliman; Duski Samad; Andri Ashadi (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2026)
This study examines the model and achievements of zakat management during the reign of Caliph Umar bin Abdul Aziz (717–720 AD), known as a period of socio-economic reform in Islamic history. Umar bin Abdul Aziz succeeded in establishing a transparent, fair, and effective zakat system, so that poverty was almost nonexistent in his territory. In addition, this study also examines various problems in zakat management in Indonesia and presents solutions or suggestions for zakat management in Indonesia. This study uses a historical-descriptive approach through a review of classical and contemporary literature. The results show that the success of zakat management during Umar bin Abdul Aziz's reign was due to three main factors: leadership integrity, administrative reform based on sharia, and the implementation of productive zakat distribution. Meanwhile, the main problems in zakat management today are the problem of inadequate human resources, lack of integrity in zakat management, lack of transparency and accountability, and the use of technology that is not yet optimal. The findings of Umar bin Abdul Aziz's successful zakat management are considered highly relevant as a model for zakat policy in the modern era, aimed at building a just and sustainable Islamic economy, particularly in addressing various zakat problems and managing them.